2023
DOI: 10.3389/fbioe.2023.1204472
|View full text |Cite
|
Sign up to set email alerts
|

A review of deubiquitinases and thier roles in tumorigenesis and development

Xian-Wen Liang,
Sheng-Zhong Wang,
Bing Liu
et al.

Abstract: Ubiquitin is a small protein that can be added onto target protein for inducing target degradation, thereby modulating the activity and stability of protein. Relatively, deubiquitinases (DUBs), a class catalase that can remove ubiquitin from substrate protein, provide a positive regulation of the protein amount at transcription level, post-translational modification, protein interaction, etc. The reversible and dynamic ubiquitination-deubiquitination process plays an essential role in maintaining protein homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…The regulation of ubiquitination is a reversible process that is constantly mediated by different E3 ubiquitin ligases and DUBs [ 42 ]. Accumulating evidence has showed that DUBs play an indispensable role in the occurrence and progression of cancers [ 43 47 ]. However, the potential roles of DUBs in HCC are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of ubiquitination is a reversible process that is constantly mediated by different E3 ubiquitin ligases and DUBs [ 42 ]. Accumulating evidence has showed that DUBs play an indispensable role in the occurrence and progression of cancers [ 43 47 ]. However, the potential roles of DUBs in HCC are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of members of the ubiquitin system, as well as the expression of their mutant proteins, has been reported in several cancer types, where they correlate with malignant progression, poor survival and prognosis [ 107 , 108 , 109 ]. Since the activity or proteolysis of several oncoproteins and tumor-suppressor proteins is impaired by the deregulation of the ubiquitin system in cancer [ 48 ], numerous biological processes are altered, including the cell cycle [ 15 , 51 , 110 ], cell invasion and metastasis [ 110 , 111 ], cancer metabolism [ 112 , 113 ], cancer stem cell stemness [ 113 , 114 ], immunological tumor microenvironment [ 113 ], immune evasion [ 51 ], tumor-promoting inflammation [ 51 ] and evasion from apoptosis [ 51 , 110 ].…”
Section: Aberrant Ubiquitination In Cancermentioning
confidence: 99%
“…Defects in deubiquitination have effects on the NF-kB, AKT and BRCA signaling pathways [ 119 ]. For a more comprehensive description of the role of the ubiquitination system in cancer development and progression, readers are referred to specific reviews [ 15 , 51 , 110 , 111 , 112 , 113 , 114 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ].…”
Section: Aberrant Ubiquitination In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the type of polyubiquitin chain formed, ubiquitination can direct the substrate to multiprotein complexes or target it for degradation via proteasomes 8 . This process is dynamic and reversible relying on deubiquitinases to remove ubiquitin and stabilize substrate proteins 9 . In the context of cancer development, ubiquitination plays a pivotal role, such as angiogenesis, apoptosis, metastasis, and immunity through its diverse effects on transcription, post-translation modifications, and protein levels 8 .…”
Section: Introductionmentioning
confidence: 99%